Implementation of 21st Century Soft Skills in Vocational High Schools to Face the Workforce - Tisa, Tisa; Asriati, Nuraini; Syamsuri, Syamsuri (Pusdikra-Publishing.com, 2024)
SMK must prepare students to enter the world of work with a better competitive advantage. Soft skills are one of the important keys in the modern world of work. Therefore, SMKs need to pay attention to the development of soft skills in students so that they are ready to face future challenges in the industrial world and the business world. This study aims to analyze the types and methods of developing soft skills that are implemented in Vocational High Schools. The research method used is qualitative research with a library research approach. The results of the study revealed that: The process of learning soft skills is not only knowledge delivery but must be able to create competent students both personally and interpersonally with the development of a soft skills curriculum in Vocational High Schools (SMK), the types of soft skills that need to be developed in the SMK Curriculum include the ability communication, cooperation, leadership, and adaptability. By implementing the right soft skill development strategy.